ANALISA KESUKSESAN LEARNING MANAGEMENT SYSTEM (Studi Kasus: USD Yogyakarta) - Sriwindono, Haris; Tumiwa, Frisca (Media Teknika, 2016)
Utilization Learning Management System in college used to improve learning services to students. The purpose of this study to examine the variables and indicators that affect the success of LMS systems with exelsa USD as a case study. The model used in this study was adapted from the model of success of DeLone-McLean. Questionnaires were distributed to the students and the samples taken by stratified random sampling, and obtained 448 respondents. Data were processed using Structured Equation Modeling, and conducted tests on the measurement model and the model structure. The variables used in this study is the quality system, the quality of information, emakaian, user satisfaction, individual impact and organizational impact. From the results of this study showed that the quality system and quality of existing information on LMS exelsa very influential on the use and satisfaction of users, the use of the system is not felt by the wearer have a positive impact on the individual, but the satisfaction in use that have a positive impact on individuals, as well as the individual impact seen also influence / impact positively on the organization (in this case the university).